Testing times: identifying puberty in an identified skeletal sample - Charlotte Y. Henderson; Cristina Padez (Taylor & Francis Group, 2017)
Background: Identifying the onset of puberty in skeletal remains can provide evidence of social changes associated with the onset of adulthood. Aim: This paper presents the first test of a skeletal method for identifying stages of development associated with the onset of puberty in a skeletal sample of known age and cause of death. Materials and methods: Skeletal methods for assessing skeletal development associated with changes associated with puberty were recorded in the identified skeletal collection in Coimbra, Portugal. Historical data on the onset of menarche in this country are used to test the method. Results: As expected, females mature faster than their male counterparts. There is some side asymmetry in development. Menarche was found to have been achieved by an average age of 15. Conclusions: Asymmetry must be taken into account when dealing with partially preserved skeletons. Age of menarche is consistent, although marginally higher, than the age expected based on historical data for this time and location. Skeletal development in males could not be tested against historical data, due to the lack of counterpart historical data. The ill health known to be present in this prematurely deceased population may have delayed skeletal development and the onset of puberty.